Orthodontic Management of Impacted Premolars: A Case Report - Chaudhary, Nabin Kumar (Nepal Journal of Health Sciences, 2024)
The lip bumper can lessen the need for extractions, by distal tipping the molars and expanding the width, depth, and circumference of the arch. This case report describes how a lip bumper appliance followed by fixed orthodontic treatment helped a patient with insufficient space for the eruption of permanent teeth due to mesial drift of the molars. This case report successfully showed that the lip bumper can be used for the effective up righting of molars to regain the lost space.